THE TRANSFER OF INDIAN MEDICAL KNOWLEDGE TO THE MUSLIM WORLD - Ruhollah Bahrami (تاریخ اسلام)
India was a brilliant center of knowledge and civilization in the ancient world; and Indian medicine was a deeply rooted scientific discipline in those days. This discipline had been mixed with religious teachings of ancient Indians, and in its earliest stages with Indian magic and superstition. Nature, India’s diverse plant covering and its employment for natural and herbal cure of various pains, plus the mixing of primitive forms of medicine with spiritual and religious phenomena caused Indian medicine to appear in different forms from voodoo medicine and exorcism to acupuncture and herbotherapy. These different methods of medical practice were highly influential at the time gaining the attention of ancient scientific centers including those in Iran. The Indian medical heritage, particularly since the age of the Iranian King Khosrow II Anushirvan, entered such scientific centers as the University of Jundi-Shapur, and was combined with other medical schools such as the Iranian, Greek and Babylonian traditions. Following the advent of Islam and early Muslim conquests, this scientific heritage wastransferred to the Muslim World. The writer has tried here to demonstrate the position of Indian medical knowledge and the role of India’s physicians in the spread of Indian medical tradition to the Muslim World, and especially to the court of the ‘Abbasid caliphs.